2013
DOI: 10.1155/2013/674106
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota, Microinflammation, Metabolic Profile, and Zonulin Concentration in Obese and Normal Weight Subjects

Abstract: The association between gut microbiota and circulating zonulin level, a marker of intestinal permeability, has not been studied yet. The aim of the study is the assessment of plasma zonulin, haptoglobin and proinflammatory cytokines (TNF-α and IL-6) levels in relation to composition of gut microbiota in obese and normal weight subjects. Circulating inflammation markers, such as TNF-α, sTNFR1, sTNFR2, IL-6, zonulin, and haptoglobin levels were measured and semiquantitative analysis of gut microbiota composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
77
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(94 citation statements)
references
References 28 publications
13
77
0
4
Order By: Relevance
“…Zonulin is a regulator of tight junction function in humans and serum levels correlate with in vivo gut permeability assessed by lactulose/mannitol test [46]. The serum zonulin increase observed in our study is in accordance with recent studies in PCOS patients and obese individuals, where serum zonulin was correlated with measures of insulin resistance and fecal bacterial colony count [21,47]. Serum endotoxin and hsCRP did not differ significantly between patients and controls.…”
Section: Discussionsupporting
confidence: 90%
“…Zonulin is a regulator of tight junction function in humans and serum levels correlate with in vivo gut permeability assessed by lactulose/mannitol test [46]. The serum zonulin increase observed in our study is in accordance with recent studies in PCOS patients and obese individuals, where serum zonulin was correlated with measures of insulin resistance and fecal bacterial colony count [21,47]. Serum endotoxin and hsCRP did not differ significantly between patients and controls.…”
Section: Discussionsupporting
confidence: 90%
“…In our study; we did not find any correlation to the severity of steatosis assessed by liver ultrasound; however, we found that it was correlated with intestinal inflammation markers. Similar results were found by Zak-Gołąb A et al (13); zonulin concentration was correlated with intestinal inflammation and systemic microinflammation in obese subjects.…”
Section: Discussionsupporting
confidence: 90%
“…In a study conducted by Zhang et al (5) on three adult patient groups with normal glucose tolerance, impaired glucose tolerance, and type 2 diabetes mellitus, zonulin was found to have a positive correlation with IR. However, Zak-Golab et al (27) could not demonstrate any relationship between zonulin levels and IR in obese adult patients and interpreted their results to be due to the small sample size and also to their inability to use oral glucose tolerance test (OGTT) instead of the HOMA-IR index in the evaluation of IR. Zonulin, which is considered a marker of intestinal permeability, is suggested to play a role in the development of the metabolic syndrome (IR, type 2 diabetes mellitus, and dyslipidemia) found in obese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating the relationship between zonulin, which has an effect on increased intestinal permeability, and IR, have yielded varying results (3,5,27). Moreno-Navarrete et al (3) were the first to investigate the association between zonulin and IR and demonstrated that serum zonulin levels were significantly higher in obese individuals when compared to non-obese individuals.…”
Section: Discussionmentioning
confidence: 99%